Common complications and their managements after penoscrotal hypospadias repairs: comparison of one-stage and staged repairs - Ozcakir, Esra; Okay, Sefer Tolga; Kaya, Mete (The European Research Journal, 2022)
Objectives: Surgical repair of hypospadias is challenging and the risk of complications is high, even for the most experienced specialists. In this study, we aim to present our experience with the management of the most common postoperative complications in patients who underwent proximal hypospadias repair. Methods: We retrospectively reviewed the data of patients underwent proximal hypospadias surgery between December 2011 and February 2021. Patients who were repaired with single and staged methods were divided into two groups. Treatment methods of postoperative complications including wound dehiscence, fistula, stricture and diverticulum were examined and the results were noted and statistically compared. Results: Forty-four patients, with a mean age of 34 months at the first surgery were reviewed, 17 of whom underwent a single-stage repair and 27 of whom staged. Except for a patient who underwent Onlay island flap urethroplasty, long TIPU was used in all single-session repairs, and Byar’s and Bracka methods in 19 and 8 patients of the staged group, respectively. The overall complication rate was 34% at a mean follow-up of 41 months, and 18% in single-stage repair, and 44% in staged. Glans dehiscence, urethrocutaneous fistula, urethral stricture, and diverticula were seen 2 (4%), 4 (9%), and 4 (9%), respectively. All glans dehiscence and two fistulae along with distal stricture treated with Mathieu urethroplasty. Two proximal short strictures were relieved by single session dilation. Diverticula were repaired by urethroplasty. The complications were successfully treated, and no recurrence developed. Conclusions: The risk of complications is higher due to proximal hypospadias, long urethroplasty and defective penile tissue. Hypoplasic glandular urethra, distal stricture and a neourethra devoid of spongiosum appear to be related for complications. Despite the more encountered, postoperative complications of proximal hypospadias repairs have been shown to be successfully treated with the appropriate techniques.